The moderating role of work engagement in relationship between person–supervisor fit and organizational citizenship behavior among Muslim government servants in Wisma Persekutuan Kota Bharu: A pilot study - Abdullah Thani, Ayu Kamareenna; Rosely, Nurhidayah; Sakarji, Siti Rosnita; Aminuddin, Azwan Shah; Mohd Firdaus Kozako, Intan Nurul’Ain (Journal of Islamic, Social, Economics and Development, 2026)
This pilot study examines the relationship between person–supervisor fit and organizational citizenship behavior (OCB), and the moderating role of work engagement among Muslim government servants at Wisma Persekutuan Kota Bharu. Data were collected from 30 respondents using an online questionnaire administered via Google Forms. Measurement instruments for person–supervisor fit and OCB were adopted from Abdullah Thani (2019), while work engagement was measured using a validated scale. Data were analyzed using IBM SPSS Statistics version 28, employing descriptive statistics, reliability analysis, correlation, and hierarchical regression. Results indicated that person–supervisor fit was positively associated with OCB and that work engagement significantly moderated this relationship, strengthening the effect of supervisor compatibility on discretionary work behavior. All constructs demonstrated satisfactory reliability coefficients exceeding the recommended threshold of 0.70. These findings support the feasibility of the instruments and procedures for a larger-scale study and contribute to the literature on supervisor relationships, engagement, and citizenship behavior in the Malaysian public sector.